Kewenangan Pengawasan Kepala Dusun Dalam Pelaksanaan Pembangunan di Desa Bawang Kecamatan Bawang Kabupaten Batang - Rayhan, Ahmad; Farhan, Muhammad Ikhlasul; Fasyehhudin, Mohamad (IAIN Metro, 2024)
Various aspects of social change planned through development are realized through the village government. In villages, hamlets or other names can be formed that are adapted to the origins, customs and socio-cultural values ​​of the community. A hamlet is a part of the area within a village where the work environment of village government is implemented. The hamlet head has the authority to supervise the implementation of development in his area. The implementation of development in the hamlet area in Bawang Village is directly supervised by the village head. In his daily life, the hamlet head in Bawang Village carries out delegative tasks given by the village head. Based on this, the identification of the problem in this research is regarding the supervisory authority of the hamlet head of Bawang Village, Bawang District, Batang Regency in implementing development in his area, as well as the constraints and obstacles in supervising the implementation of development in Bawang Village, Bawang District, Batang Regency. The method used in this research is an empirical juridical approach, with the research specifications used being analytical descriptive. The data sources used in this research are secondary data sources and primary data sources. The supervisory authority of the hamlet head in the implementation of development has been implemented. This authority has not been implemented optimally so more structured coordination is needed within the Bawang Village government. The obstacles in implementing development include lack of knowledge of employees in carrying out work, budget allocation, unpredictable weather, and lack of maximum community participation in implementing development.